Value chain management as a tool for service company - Vergiú Canto, Jorge (2013)
The cleaning service companies generally get customers through public tenders, becoming the immediacy with which it presents the quote and the cost of service on key factors. Many times the cost is determined based on past services (estimates), which has repeatedly caused the cancellation of the service, or the service given, generating losses, which are evidenced recently at the end of the period, i.e. when the service contract has been signed and the economic and operating conditions cannot be changed, resulting in many opportunities to renegotiate the contract or cease certain activities according to frequency. To that extent the author tries to show a management tool that integrates decision factors, providing valuegenerating responses in real time, allowing to know the economic and financial situation of the company. As a result of this process was demonstrated deficits in a business unit and identified the activities of the value chain of the company more expensive that require review.